Scavenging agent for bead effect on back surface of ceramic tile and preparation method thereof
By using scavengers containing components such as silane coupling agent and acrylate-tert-vinyl carbonate copolymer latex powder, the problem of reducing adhesion caused by the back of the tile is solved, and the effect of improving the bonding performance of the tile and extending the service life is achieved.
Patent Information
- Application Number
- CN202411741623.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The lot bead effect on the back of the tiles causes the adhesion between the tiles and the floor to be reduced, which is prone to hollowing and cracking, affecting the laying effect and service life, and increasing maintenance costs.
A scavenger including silane coupling agent, acrylate-tert-vinyl carbonate copolymer latex powder, silica nanoparticles, alkaline components, bio-based surfactants, lipases, adsorbents and fillers is used to reduce surface tension and enhance bonding strength through hydrolysis reactions and formation of polymer films.
Effectively remove the lot bead effect on the back of the tiles, improve the adhesion between the tiles and the floor, reduce hollowing rate, extend service life, and is low in cost and simple in use. It is suitable for different types of tiles and construction environments.
Smart Images

Figure BDA0005162724030000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a bead effect remover on the back of a tile and a preparation method thereof. Background Art
[0002] The lotus bead effect on the back of the tile means that when water drops fall on the back of the tile, it will not spread out, but form small water drops, and these water drops can roll on the surface and are not easy to adhere. This phenomenon is mainly due to the hydrophobicity or super hydrophobicity of the back of the tile. The main reasons for this phenomenon are: 1. Release agent: In the manufacturing process of tiles, in order to facilitate the removal of the finished product from the mold, a layer of release agent is often applied inside the mold or on the back of the tile. This layer of release agent may contain wax components or other hydrophobic materials, making the back of the tile highly hydrophobic. 2. Surface roughness: If the back of the tile becomes very smooth after special treatment, or a micro-nano structure similar to the "lotus effect" is formed on its microstructure (that is, there are small protrusions arranged regularly on the surface), it will also promote the water droplets to form a ball and roll, which is not easily absorbed by the tile. 3. Chemical residues: In addition to the specially used release agent, there may be other types of chemical residues in the production process, such as antifouling agents, polishing agents, etc. These substances can also give the back of the tile a certain hydrophobic property.
[0003] The bead effect on the back of the tile will reduce the adhesion between the tile and the ground, causing the tile to be easily hollow and cracked, seriously affecting the paving effect and service life, and also increasing the maintenance cost. Therefore, it is very important to solve the bead effect problem on the back of the tile in a timely manner.
[0004] Patent CN202410290030.4 discloses a treatment agent that overcomes the hydrophobic / super-hydrophobic problem of the bottom surface of building ceramics, including: 0.2-1.5% node agent, 0.5-4% film former, 0.1-0.6% carboxymethyl cellulose, 0.1-0.8% plasticizer, 0.5-6% silica sol, and 85-98% water. The interface layer prepared by the treatment agent disclosed in the patent can effectively prevent oily / organic wax water from directly depositing on the bottom of the brick, thereby solving the hydrophobic / super-hydrophobic problem of the bottom surface. However, the iron-based metal organic framework material (MOF) used in the treatment agent as a node agent will increase the cost of the treatment agent, and its synthesis process is relatively complicated, which directly affects the industrial production of the final product. The treatment agent requires specific spraying equipment and conditions (such as nozzle aperture, spraying pressure, etc.), which increases the complexity of construction and the requirements for operators. The curing process needs to be carried out at 80-100°C, which means that heating equipment is required at the construction site or compressed air drying is used, increasing construction time and cost.
[0005] Therefore, there is an urgent need for a low-cost, simple-to-use remover that can effectively remove the beading effect on the back of tiles. Summary of the invention
[0006] The purpose of the present invention is to provide a beading effect remover on the back of a tile and a preparation method thereof. The remover has low preparation cost and is simple to use. It can effectively remove the beading effect on the back of the tile, improve the adhesion between the tile and the ground, solve the problem that the tile is prone to hollowing and cracking, improve the laying effect of the tile, and extend the service life of the tile.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention provides a beading effect remover for the back of a tile, comprising the following components in mass percentage: 0.5-5% of a silane coupling agent, 2-10% of an acrylate-versatate vinyl carbonate copolymer latex powder, 1-8% of silica nanoparticles, 8-20% of an alkaline component, 3-10% of a bio-based surfactant, 1-5% of a lipase, 8-20% of an adsorbent, and 40-70% of a filler.
[0009] In a preferred embodiment, the beading effect remover on the back of the tile includes the following components in mass percentage: 0.5-2% silane coupling agent, 3-5% acrylate-versatate vinyl carbonate copolymer latex powder, 2-4% silica nanoparticles, 10-15% alkaline component, 5-8% bio-based surfactant, 1-2% lipase, 10-15% adsorbent, and 60-70% filler.
[0010] In a preferred embodiment, the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0011] In a preferred embodiment, the preparation method of the butyl acrylate-vinyl acetate copolymer latex powder is as follows:
[0012] (1) Add deionized water to a reaction kettle, heat to 60-80° C., add sodium lauryl sulfate and polyvinyl alcohol, stir evenly, and add sodium bicarbonate to adjust the pH value to 7-8;
[0013] (2) mixing butyl acrylate and vinyl acetate monomers to form a monomer mixture, and adding a portion of the monomer mixture into a reaction kettle for pre-emulsification;
[0014] (3) adjusting the temperature of the reactor to 70-80° C., and respectively adding the remaining monomer mixture and potassium persulfate aqueous solution to the reactor for 1-2 hours. After the addition is completed, the reaction is continued at a temperature of 1-2 hours. After the reaction is completed, the heating is stopped, and the mixture is cooled to room temperature to obtain the desired feed solution;
[0015] (4) Drying the above-mentioned liquid by spray drying equipment to obtain the butyl acrylate-vinyl acetate copolymer latex powder.
[0016] In a preferred embodiment, the mass ratio of butyl acrylate to vinyl acetate is 1.5 to 3:1.
[0017] In a preferred embodiment, the mass of the sodium dodecyl sulfate is 1-5% of the total amount of monomers, the mass of the polyvinyl alcohol is 0.5-3% of the total amount of monomers, and the mass of the potassium persulfate is 0.1-0.5% of the total amount of monomers.
[0018] In a preferred embodiment, the mass of the partial monomer mixture in step (2) is 10 to 30% of the total mass of the monomer mixture.
[0019] In the remover provided by the present invention, the silane coupling agent forms a layer of hydrophilic silanol groups on the surface of the tile through a hydrolysis reaction, which increases the wettability of the surface, reduces the surface tension of the tile surface, makes it easier for water to spread, and reduces the beading effect. At the same time, it can react with the active groups (such as hydroxyl groups) in the tile adhesive to form stable chemical bonds and improve the bonding strength. The butyl acrylate-vinyl acetate copolymer latex powder forms a continuous polymer film on the surface of the tile, providing good adhesion and water resistance. The formed polymer film also has certain flexibility and strength, which can improve the mechanical bonding between the tile and the adhesive, thereby improving the overall tensile bonding strength. Nano-scale silica particles increase the roughness of the tile surface and improve the wettability and bonding properties of the surface. Silica nanoparticles have a very large specific surface area, which allows them to be evenly dispersed in the latex powder, forming a unique three-dimensional network structure with the polymer latex powder, and can effectively penetrate into the back of the tile and the wall base, so that the tile adhesive forms a cavity-free adhesive system with the base and the tile. At the same time, the stability of the silica nanoparticles ensures the bonding strength of the tile under water immersion and thermal aging conditions. At the same time, the silane coupling agent with a smaller molecular weight can easily penetrate into the tiny pores on the back of the tile and the wall base, and work together with the silica nanoparticles and latex powder to form a closer contact, making the surface smoother, reducing water penetration, and forming a cavity-free adhesive system. The silane coupling agent works together with the silica nanoparticles and the acrylate-versatate copolymer latex powder to significantly improve the bonding performance of the tile, especially the bonding strength under water immersion and thermal aging conditions, thereby effectively reducing the hollowing rate of the tile.
[0020] In a preferred embodiment, the alkaline component is selected from one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium silicate, trisodium phosphate, and potassium hydroxide.
[0021] In a preferred embodiment, the bio-based surfactant is a mixture of lignin sulfonate and fatty acid methyl ester sulfonate, and the mass ratio of the two is 1:1-3.
[0022] Bio-based surfactants reduce surface tension, making it easier for water to spread on the tile surface. At the same time, lipase breaks down oil and grease contaminants on the surface, further improving the wettability of the surface. These two effects work together to enhance the wettability of the tile surface and reduce the beading effect. Bio-based surfactants use a mixture of lignin sulfonate and fatty acid methyl ester sulfonate in a specific ratio to help other ingredients (such as silica nanoparticles and acrylate-versatate copolymer latex powder) disperse evenly in water, while lipase reduces the uneven deposition of these ingredients on the surface by breaking down grease. This dual action ensures that all ingredients are evenly distributed on the tile surface and improves overall performance. In addition, the use of a mixture of lignin sulfonate and fatty acid methyl ester sulfonate can further improve the stability of the product under different pH and temperature conditions, help maintain the long-term stability of the product, and reduce agglomeration.
[0023] In a preferred embodiment, the adsorbent is obtained by mixing diatomaceous earth and montmorillonite, which are modified and then mixed with carboxymethyl cellulose.
[0024] In a preferred embodiment, the modification method is as follows:
[0025] (1) weighing diatomaceous earth, montmorillonite and carboxymethyl cellulose in proportion, and mixing the diatomaceous earth with the montmorillonite;
[0026] (2) treating the mixture at 500-600° C. for 2-5 hours, and cooling to room temperature after the treatment;
[0027] (3) adding the heat-treated mixture into 1 M HCl at a solid-liquid ratio of 1:8-15 g / mL and stirring for 1-2 hours;
[0028] (4) filtering and washing with deionized water until the pH is neutral, drying and then mixing with carboxymethyl cellulose to obtain an adsorbent.
[0029] In a preferred embodiment, the mass ratio of the diatomaceous earth, montmorillonite and carboxymethyl cellulose is 4-5:3-4:1.
[0030] Modified diatomaceous earth and montmorillonite mixed with carboxymethyl cellulose as adsorbents can further enhance the adsorption capacity of the material, improve dispersibility and stability, and enhance mechanical cleaning ability. Heat treatment of the mixture of diatomaceous earth and montmorillonite can change the surface properties and pore structure of the material, thereby enhancing its adsorption capacity and thermal stability. Acid treatment can change the surface charge characteristics, increase porosity, and improve the selective adsorption of specific pollutants such as grease on the back of the tile.
[0031] In a preferred embodiment, the filler is selected from one or more of kaolin, calcium carbonate and talc.
[0032] The alkaline component in the remover formula can neutralize the acidic substances that may be present on the tile surface, and can also act as a mild abrasive to help remove dirt and grease from the surface. Fillers can reduce costs and help adjust the overall properties of the mixture, providing certain mechanical strength and stability.
[0033] The second aspect of the present invention provides a method for preparing the above-mentioned beading effect remover on the back of a tile, comprising the following steps:
[0034] (1) Weigh each raw material component by weight;
[0035] (2) mixing the silane coupling agent with 20 to 40% by mass of an adsorbent so that the silane coupling agent is completely absorbed by the adsorbent;
[0036] (3) adding the remaining adsorbent, filler, alkaline component, and acrylate-versatate copolymer latex powder into a stirrer and stirring for 5 to 10 minutes;
[0037] (4) adding the silica nanoparticles and the bio-based surfactant to the agitator of step (3) and continuing to stir for 10 to 20 minutes;
[0038] (5) Add the lipase and the silane coupling agent / adsorbent mixture treated in step (2) to the stirrer in step (4) and continue stirring for 10 to 20 minutes to obtain the scavenger.
[0039] The method of using the bead effect remover on the back of the tile of the present invention is as follows: disperse the remover in water, then spray it directly on the back of the tile, and after it acts for 10 to 20 minutes, wipe it with a towel and then apply glue and lay it. 100g of the remover is mixed with about 20kg of water, and 140 square meters of tiles can be cleaned.
[0040] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0041] 1. The bead effect remover of the present invention can effectively remove the bead effect on the back of the ceramic tile, improve the bonding performance of the ceramic tile, improve the durability, especially the bonding performance of the ceramic tile after immersion in water and heat aging, reduce the hollowing phenomenon, and increase the service life of the ceramic tile.
[0042] 2. The formula of the lotus bead effect remover of the present invention has low cost, readily available raw materials, low toxicity and environmental protection, and is suitable for different types of tiles and construction environments.
[0043] 3. The method of using the bead effect remover of the present invention is simple and quick, which improves the construction efficiency and quality, is easy to operate, saves costs, and enhances safety and environmental protection. DETAILED DESCRIPTION
[0044] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.
[0045] The following sources of raw materials are provided for illustrative purposes:
[0046] Silica nanoparticles were purchased from Xi'an Qiyue Biotechnology Co., Ltd. with a particle size of 80-100 nm.
[0047] Lipase was purchased from Jiangsu Libin Bioengineering Co., Ltd. with an enzyme activity parameter of 50,000 U / g.
[0048] Diatomaceous earth and montmorillonite were purchased from Shuntian Mineral Products Processing Plant in Lingshou County, and the average particle size was 200 mesh.
[0049] Carboxymethyl cellulose was purchased from Hebei Chenming Biotechnology Co., Ltd.
[0050] Calcium lignin sulfonate was purchased from Shandong Chenming Paper Group Co., Ltd., model number CMC-LS.
[0051] Fatty acid methyl ester sulfonate was purchased from Jiangsu Hai'an Petrochemical Plant, model MES-70.
[0052] Calcium carbonate was purchased from Anhui Huasu Co., Ltd., model HS-325, with an average particle size of 45 μm.
[0053] Polyvinyl alcohol was purchased from Shanghai Huayi Group, model number 1788.
[0054] Example 1
[0055] The present embodiment provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1% of a silane coupling agent, 4% of an acrylate-versatate vinyl carbonate copolymer latex powder, 3% of silica nanoparticles, 10% of an alkaline component, 6% of a bio-based surfactant, 1% of a lipase, 10% of an adsorbent, and 65% of a filler.
[0056] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0057] The alkaline component is sodium bicarbonate;
[0058] The bio-based surfactant is a mixture of calcium lignin sulfonate and fatty acid methyl ester sulfonate in a mass ratio of 1:2;
[0059] The filler is calcium carbonate;
[0060] The preparation method of the adsorbent is as follows:
[0061] (1) diatomaceous earth, montmorillonite and carboxymethyl cellulose are weighed in a mass ratio of 4:3:1, and the diatomaceous earth and montmorillonite are mixed;
[0062] (2) treating the mixture at 600° C. for 3 hours and cooling it to room temperature after the treatment;
[0063] (3) adding the heat-treated mixture into 1 M HCl at a solid-liquid ratio of 1:10 g / mL and stirring for 1 hour;
[0064] (4) filtering and washing with deionized water until the pH is neutral, drying and then mixing with carboxymethyl cellulose to obtain an adsorbent.
[0065] The preparation method of the acrylate-versatate vinyl carbonate copolymer latex powder is as follows:
[0066] (1) Add 50 mL of deionized water to a reaction kettle, heat to 70° C., add 0.5 g of sodium dodecyl sulfate, stir, then add 0.2 g of polyvinyl alcohol, stir, and add sodium bicarbonate to adjust the pH value to 7.5;
[0067] (2) 7 g of butyl acrylate and 3 g of vinyl acetate were mixed and stirred to form a monomer mixture, and 2 g of the monomer mixture was added to a reaction kettle for pre-emulsification;
[0068] (3) 0.02 g of potassium persulfate was dissolved in 20 mL of deionized water to form a potassium persulfate aqueous solution, the temperature of the reactor was adjusted to 80° C., and the potassium persulfate aqueous solution and the remaining monomer mixture were slowly added dropwise to the reactor for 1 hour. After the addition was completed, the reaction was continued at room temperature for 2 hours. After the reaction was completed, the heating was stopped and the reaction was cooled to room temperature to obtain the desired feed solution;
[0069] (4) Drying the above-mentioned liquid by spray drying equipment to obtain the butyl acrylate-vinyl acetate copolymer latex powder.
[0070] The preparation method of the scavenger is as follows:
[0071] (1) Weigh the above raw material components by weight;
[0072] (2) 1 g of γ-aminopropyltriethoxysilane was mixed with 3 g of an adsorbent so that the silane was completely absorbed by the adsorbent;
[0073] (3) adding calcium carbonate, remaining adsorbent, sodium bicarbonate, and acrylate-versatate copolymer latex powder into a stirrer and stirring for 5 minutes;
[0074] (4) adding the silica nanoparticles and the bio-based surfactant to the stirrer of step (3) and continuing stirring for 10 minutes;
[0075] (5) Add the lipase and the γ-aminopropyltriethoxysilane / adsorbent mixture treated in step (2) into the stirrer in step (4) and continue stirring for 10 minutes to obtain the scavenger.
[0076] Example 2
[0077] The present embodiment provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1.5% silane coupling agent, 4% acrylate-versatate vinyl carbonate copolymer latex powder, 2% silica nanoparticles, 12% alkaline component, 8% bio-based surfactant, 1.5% lipase, 11% adsorbent, and 60% filler.
[0078] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0079] The alkaline component is sodium hydroxide;
[0080] The bio-based surfactant is a mixture of calcium lignin sulfonate and fatty acid methyl ester sulfonate in a mass ratio of 1:3;
[0081] The filler is kaolin;
[0082] The preparation method of the adsorbent and acrylate-versatate vinyl carbonate copolymer latex powder is the same as that in Example 1;
[0083] The preparation method of the scavenger is the same as that of Example 1.
[0084] Example 3
[0085] The present embodiment provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 2% silane coupling agent, 3% acrylate-versatate vinyl carbonate copolymer latex powder, 3% silica nanoparticles, 15% alkaline component, 5% bio-based surfactant, 1% lipase, 10% adsorbent, and 61% filler.
[0086] The silane coupling agent is γ-methacryloxypropyltrimethoxysilane;
[0087] The alkaline component is sodium hydroxide;
[0088] The bio-based surfactant is a mixture of calcium lignin sulfonate and fatty acid methyl ester sulfonate in a mass ratio of 1:1;
[0089] The filler is kaolin;
[0090] The preparation method of the adsorbent and acrylate-versatate vinyl carbonate copolymer latex powder is the same as that in Example 1;
[0091] The preparation method of the scavenger is the same as that of Example 1.
[0092] Comparative Example 1
[0093] This comparative example provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1% of a silane coupling agent, 4% of an acrylate-versatate vinyl carbonate copolymer latex powder, 10% of an alkaline component, 6% of a bio-based surfactant, 1% of a lipase, 10% of an adsorbent, and 68% of a filler.
[0094] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0095] The alkaline component is sodium bicarbonate;
[0096] The bio-based surfactant is a mixture of calcium lignin sulfonate and fatty acid methyl ester sulfonate in a mass ratio of 1:2;
[0097] The filler is calcium carbonate;
[0098] The preparation methods of the adsorbent and acrylate-versatate vinyl carbonate copolymer latex powder are the same as those in Example 1.
[0099] In the method for preparing the scavenger, no silicon dioxide nanoparticles are added in step (4), and the rest is the same as in Example 1.
[0100] Comparative Example 2
[0101] This comparative example provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1% silane coupling agent, 4% acrylate latex powder, 3% silica nanoparticles, 10% alkaline component, 6% bio-based surfactant, 1% lipase, 10% adsorbent, and 65% filler.
[0102] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0103] The alkaline component is sodium bicarbonate;
[0104] The bio-based surfactant is a mixture of calcium lignin sulfonate and fatty acid methyl ester sulfonate in a mass ratio of 1:2;
[0105] The filler is calcium carbonate;
[0106] The preparation method of the adsorbent is the same as that of Example 1;
[0107] In the preparation method of the scavenger, in step (3), the acrylate-versatate vinyl ester copolymer latex powder is replaced with acrylate latex powder, and the rest is the same as in Example 1.
[0108] Comparative Example 3
[0109] This comparative example provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1% silane coupling agent, 4% acrylate-versatate vinyl carbonate copolymer latex powder, 3% silica nanoparticles, 10% alkaline component, 6% bio-based surfactant, 10% adsorbent, and 66% filler.
[0110] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0111] The alkaline component is sodium bicarbonate;
[0112] The bio-based surfactant is a mixture of calcium lignin sulfonate and fatty acid methyl ester sulfonate in a mass ratio of 1:2;
[0113] The filler is calcium carbonate;
[0114] The preparation method of the adsorbent is the same as that of Example 1;
[0115] The preparation method of the acrylate-versatate vinyl ester copolymer latex powder is the same as that of Example 1.
[0116] In the preparation method of the scavenger, lipase is not added in step (5), and the rest is the same as in Example 1.
[0117] Comparative Example 4
[0118] The comparative example provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1% silane coupling agent, 4% acrylate-versatate vinyl carbonate copolymer latex powder, 3% silica nanoparticles, 10% alkaline component, 6% sodium dodecyl sulfate, 1% lipase, 10% adsorbent, and 65% filler.
[0119] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0120] The alkaline component is sodium bicarbonate;
[0121] The filler is calcium carbonate;
[0122] The preparation methods of the adsorbent and acrylate-versatate vinyl carbonate copolymer latex powder are the same as those in Example 1.
[0123] In the preparation method of the scavenger, the surfactant in step (4) is sodium dodecyl sulfate, and the rest is the same as in Example 1.
[0124] Comparative Example 5
[0125] The present embodiment provides a beading effect remover for the back of a tile, comprising the following components in percentage by mass: 1% of a silane coupling agent, 12% of an acrylate-versatate vinyl carbonate copolymer latex powder, 1% of silica nanoparticles, 10% of an alkaline component, 2% of a bio-based surfactant, 1% of a lipase, 5% of an adsorbent, and 68% of a filler.
[0126] The silane coupling agent is γ-aminopropyltriethoxysilane;
[0127] The alkaline component is sodium bicarbonate;
[0128] The bio-based surfactant is lignin sulfonate;
[0129] The filler is calcium carbonate;
[0130] The preparation method of the acrylate-versatate vinyl ester copolymer latex powder is the same as that of Example 1.
[0131] The preparation method of the scavenger is the same as that of Example 1.
[0132] Performance Test:
[0133] Take 10g of the remover prepared in Examples 1-3 and Comparative Examples 1-5 respectively, disperse in 2kg of water, spray on the back of the tile, and after 10 minutes, wipe off the liquid with a towel, apply glue to the tile and pave it. The adhesive is Degao TTB II enhanced tile adhesive. The untreated group is not treated with the remover and directly applied with glue. Each group has 20 parallel samples.
[0134] The tensile bonding strength was tested according to the test method of JC / T 547-2017 "Ceramic Tile Adhesive", and the hollowing rate of tiles was tested according to GB50209-2010 "Code for Acceptance of Construction Quality of Building Floor Engineering". The test results are shown in Table 1.
[0135] Table 1: Performance Test
[0136]
[0137] The above test results show that the remover prepared by the present invention effectively improves the bonding effect of the tiles and reduces the hollowing rate of the tiles after acting on the tiles. The silica nanoparticles in the formula work together with the silane coupling agent and the acrylate-versatate copolymer latex powder to form a dual mechanism of chemical bridging and physical anchoring, further enhancing the bonding strength between the tiles and the adhesive. When the silica nanoparticles are not added in Comparative Example 1, the micropores on the surface of the tiles will not be filled, which is easy to cause the penetration of moisture and air. At the same time, due to the lack of physical anchoring points, the interfacial bonding force between the tiles and the adhesive is weakened, and it is easy to separate under the action of external forces. In addition, the wettability of the tile surface is poor, and the adhesive cannot be fully spread and penetrated, which easily forms cavities and causes hollowing phenomena, which ultimately leads to a decrease in the tensile bonding strength of the tiles treated with the prepared remover, a decrease in durability, and an increase in the hollowing rate. In Comparative Example 2, the acrylate-versatate vinyl ester copolymer latex powder is replaced with acrylate latex powder. The flexibility, water resistance, weather resistance and compatibility with ceramic tiles of the film-forming material will all decrease, causing the ceramic tiles to easily crack when subjected to stress, resulting in bonding failure and hollowing.
[0138] The lipase and lignin sulfonate / fatty acid methyl ester sulfonate in the formula work together to improve the cleanliness, wettability and interfacial bonding of the tile surface, thereby improving the bonding strength between the tile and the adhesive and reducing the hollowing rate. Therefore, the absence of lipase in Comparative Example 3 will result in the inability to effectively remove grease and other pollutants on the tile surface, resulting in the adhesive being unable to fully adhere to the tile surface, reducing the tensile bonding strength. At the same time, the wettability of the tile surface is insufficient, and the adhesive cannot fully penetrate and spread on the tile surface, resulting in poor bonding. In Comparative Example 4, the bio-based surfactant is replaced with sodium dodecyl sulfate, resulting in a decrease in the tensile bonding strength and durability of the tile. The reason may be that the dispersibility of sodium dodecyl sulfate in the system is not as good as that of lignin sulfonate / fatty acid methyl ester sulfonate, resulting in aggregation or uneven distribution of the formula components, affecting the overall performance. At the same time, sodium dodecyl sulfate may not be as stable as lignin sulfonate / fatty acid methyl ester sulfonate during long-term use, and is easily affected by environmental factors, resulting in a decrease in bonding performance.
[0139] Changing the formula ratio in Comparative Example 5 also led to a decrease in the tensile bonding strength and durability of the tiles, proving that the ratio of the formula of the present invention has an important influence on the product effect. Improper proportions of the ingredients will lead to weakened interfacial bonding, especially improper proportions of bio-based surfactants, silane coupling agents and copolymer latex powders, which will affect the bonding effect; improper proportions of copolymer latex powders and silica nanoparticles may lead to a decrease in the mechanical properties of the coating and reduce the tensile bonding strength; improper proportions of bio-based surfactants and lipases may lead to insufficient wettability, and the adhesive cannot fully penetrate and spread on the surface of the tile, increasing the risk of hollowing; improper proportions of silane coupling agents and silica nanoparticles may lead to weakened interfacial bonding, and easy separation under the action of external forces, leading to hollowing; improper proportions of copolymer latex powders and other ingredients may lead to a decrease in water resistance and weather resistance of the coating, increasing the risk of hollowing.
[0140] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A bead effect remover on the back of a tile, characterized in that: The invention comprises the following components in percentage by mass: 0.5-5% of silane coupling agent, 2-10% of acrylate-versatate vinyl carbonate copolymer latex powder, 1-8% of silicon dioxide nanoparticles, 8-20% of alkaline component, 3-10% of bio-based surfactant, 1-5% of lipase, 8-20% of adsorbent and 40-70% of filler.
2. The beading effect remover on the back of a tile according to claim 1, characterized in that: The invention comprises the following components in percentage by mass: 0.5-2% of silane coupling agent, 3-5% of acrylate-versatate vinyl carbonate copolymer latex powder, 2-4% of silicon dioxide nanoparticles, 10-15% of alkaline component, 5-8% of bio-based surfactant, 1-2% of lipase, 10-15% of adsorbent and 60-70% of filler.
3. The beading effect remover on the back of a tile according to claim 1, characterized in that: The silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
4. The beading effect remover on the back of a tile according to claim 1, characterized in that: The butyl acrylate-vinyl acetate copolymer latex powder is prepared as follows: (1) Add deionized water to a reaction kettle, heat to 60-80° C., add sodium lauryl sulfate and polyvinyl alcohol, stir evenly, and add sodium bicarbonate to adjust the pH value to 7-8; (2) mixing butyl acrylate and vinyl acetate monomers to form a monomer mixture, and adding a portion of the monomer mixture into a reaction kettle for pre-emulsification; (3) adjusting the temperature of the reactor to 70-80° C., and respectively adding the remaining monomer mixture and potassium persulfate aqueous solution to the reactor for 1-2 hours. After the addition is completed, the reaction is continued at a temperature of 1-2 hours. After the reaction is completed, the heating is stopped, and the mixture is cooled to room temperature to obtain the desired feed solution; (4) Drying the above-mentioned liquid by spray drying equipment to obtain the butyl acrylate-vinyl acetate copolymer latex powder.
5. The beading effect remover on the back of a tile according to claim 4, characterized in that: The mass ratio of butyl acrylate to vinyl acetate is 1.5-3:1; the mass of sodium dodecyl sulfate is 1-5% of the total monomer amount, the mass of polyvinyl alcohol is 0.5-3% of the total monomer amount, and the mass of potassium persulfate is 0.1-0.5% of the total monomer amount.
6. The beading effect remover on the back of a tile according to claim 4, characterized in that: The mass of the partial monomer mixture in step (2) is 10 to 30% of the total mass of the monomer mixture.
7. The beading effect remover on the back of a tile according to claim 1, characterized in that: The bio-based surfactant is a mixture of lignin sulfonate and fatty acid methyl ester sulfonate, and the mass ratio of the two is 1:1-3.
8. The beading effect remover on the back of a tile according to claim 1, characterized in that: The adsorbent is obtained by mixing diatomaceous earth and montmorillonite and then mixing them with carboxymethyl cellulose. The modification method is as follows: (1) weighing diatomaceous earth, montmorillonite and carboxymethyl cellulose in proportion, and mixing the diatomaceous earth with the montmorillonite; (2) treating the mixture at 500-600° C. for 2-5 hours, and cooling to room temperature after the treatment; (3) adding the heat-treated mixture into 1 M HCl at a solid-liquid ratio of 1:8-15 g / mL and stirring for 1-2 hours; (4) filtering and washing with deionized water until the pH is neutral, drying and then mixing with carboxymethyl cellulose to obtain an adsorbent; The mass ratio of the diatomaceous earth, montmorillonite and carboxymethyl cellulose is 4-5:3-4:
1.
9. The beading effect remover on the back of a tile according to claim 1, characterized in that: The alkaline component is selected from one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium silicate, trisodium phosphate, and potassium hydroxide, and the filler is selected from one or more of kaolin, calcium carbonate, and talc.
10. The method for preparing the beading effect remover on the back of a tile according to any one of claims 1 to 9, comprising the following steps: (1) Weigh each raw material component by weight; (2) mixing the silane coupling agent with 20 to 40% by mass of an adsorbent so that the silane coupling agent is completely absorbed by the adsorbent; (3) adding the remaining adsorbent, filler, alkaline component, and acrylate-versatate copolymer latex powder into a stirrer and stirring for 5 to 10 minutes; (4) adding the silica nanoparticles and the bio-based surfactant to the agitator of step (3) and continuing to stir for 10 to 20 minutes; (5) Add the lipase and the silane coupling agent / adsorbent mixture treated in step (2) to the stirrer in step (4) and continue stirring for 10 to 20 minutes to obtain the scavenger.
Citation Information
Patent Citations
Treatment agent for overcoming the problem of hydrophobicity / super-hydrophobicity on the bottom surface of building ceramics causing beads, and preparation method and use method thereof
CN117886629B
BE671091A
Bonding agent capable of preventing ceramic tile hollowing or falling, and preparation method and application thereof
CN107151541A
Waterproof grout for tiles
CN110642556A
Environment-friendly tert-carbonic acid organic silicone-acrylic modified copolymer emulsion for ceramic tile back adhesive
CN111154026A
Cited By
Environment-friendly alkali swelling thickening agent for coating and preparation method of environment-friendly alkali swelling thickening agent
CN119930908A
Method for modifying back bottom surface of ceramic tile and ceramic tile prepared by using same
CN120172761A